The Bank's Authority In Determining The Value Of The Collateral Post Implementation Of The Minister Of Finance Regulation Number 228/PMK.01/2019 Concerning The Second Amendment To The Regulation Of The Minister Of Finance Number 101/PMK.01/2014 Concernin - Sang Ayu Putu Arie Indraswarawati; Sang Ayu Made Ary Kusumawardhani; Ni Putu Yunika Sulistyawati (Universitas Dwijendra Press, 2023)
Assessing collateral as an important aspect in providing credit, the fact is that the majority of internal banking appraisers are not required to fulfill the definition of competency as intended in Minister of Finance Regulation Number 228/PMK.01/2019, namely having a certification exam and further professional education, p. Another fact that is a fact is the obstacles in banking, especially in areas where there are no independent appraisal branches. The formulation of the problem raised in this research is what is the authority of collateral appraisers in carrying out collateral assessments after the issuance of changes to Minister of Finance Regulation Number 228/PMK.01/2019 and what obstacles are faced, especially by banks, after the issuance of Minister of Finance Regulation Number 228/PMK.01/2019 . This type of research is Normative legal research. This research uses a statutory approach. From this research, there is a lack of clarity regarding the implementation of Minister of Finance Regulation Number 228/PMK.01/2019 with Bank Indonesia Regulation Number 18/16/PBI/2016 so that there are still many collateral appraisers who do not meet the competency requirements in question who still carry out collateral appraisal as a basis for the credit analysis process. banking, and this will be very risky for the results of the collateral assessment both in terms of quality and also in terms of legal legality. Another thing is that banks in several regions are hampered in the credit process because there is no Public Appraisal Service Office branch which is mandatory.